Pelatihan English Speaking dan Literasi Digital bagi Santri Pondok Pesantren Al-Fudhola’ Pamekasan - Masyithah Maghfirah Rizam; Kristanti Ayuanita (PT. Riset Press International, 2026)
This community service program aimed to strengthen the English-speaking skills and digital literacy competencies of students at Pondok Pesantren Al-Fudhola’ Pamekasan. The program was initiated in response to the limited English proficiency, low confidence in speaking, and minimal digital skills observed among the students, which hindered their ability to adapt to the demands of the digital era. Using the Asset-Based Community Development (ABCD) approach, the program consisted of need analysis, training design, delivery of materials, hands-on practice, and evaluation. The activities included interactive English speaking exercises, pronunciation and vocabulary drills, social media account creation, digital content production, and practical workshops on information technology. The implementation involved university lecturers as trainers and facilitators who guided students through structured practice sessions. The results showed significant improvement in students’ confidence and ability to communicate in English, as well as increased understanding and skills in using digital tools, especially for social media-based content creation and basic digital entrepreneurship such as affiliate promotion. The program also fostered students’ motivation to apply English in daily communication and to use digital platforms productively. Overall, the community service activities successfully empowered students by integrating language skills and digital literacy, enabling them to be more competitive and adaptive to current technological developments.